6g+7=-29

Simple and best practice solution for 6g+7=-29 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6g+7=-29 equation:


Simplifying
6g + 7 = -29

Reorder the terms:
7 + 6g = -29

Solving
7 + 6g = -29

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add '-7' to each side of the equation.
7 + -7 + 6g = -29 + -7

Combine like terms: 7 + -7 = 0
0 + 6g = -29 + -7
6g = -29 + -7

Combine like terms: -29 + -7 = -36
6g = -36

Divide each side by '6'.
g = -6

Simplifying
g = -6

See similar equations:

| (2x+7)/8-2=x+(x-1)/2 | | 0=7(6-3x) | | 5.5(x-1)=0.5x+24.5 | | (t^2+7t-3)+(t^2+2t)= | | -0.3(2x-5)=0.7(6-x) | | x^3-9x^2-3x-27=0 | | 0.6x-3.6=0.6 | | (x/3)+x=(-10/9) | | x-1/6=-4/5 | | 0=-48+20p-2p^2 | | 62/20-27/10 | | 1600=16T^2 | | 3a+4=2+8 | | =1600 | | 5x^2+27x-98=0 | | 3(2x+7)=-27+6 | | -0-(-5)= | | x^4-400=0 | | 5x-1=3y+35 | | 9/2y-13=-4 | | 4x-2-7x=2(3x-7)-11x | | (27s^3(t^-6))^(1/3) | | (6x^2-5x+4)+(-2x^2+3x+1)= | | 6(x+3)-2=17-(2x-7) | | 4k^2+20k=56 | | (27s^3(t^-6))^1/3 | | 4(y+5)=2+3y | | 4/7x+7/8=-3/7x+1/4 | | 0.5x=75 | | 24t-16t^2=8 | | 1/7(x-49)=6/7 | | 2-25=0 |

Equations solver categories